Desarrollo de una aplicación de software que permita calcular los parámetros de funcionamiento de un sistema de bombeo. - Muñoz Gualán, Erik Danilo (2015)
This thesis project has the finality of develop a software app, that let us calculate the functioning parameters of a pumping system for two methods of regulations of caudal (variation method of hydraulic K lost and variation of the rotational speed of the pump), in order to reach this, it was reviewed and selected the bibliography of various important authors concerning to the topic of pumping systems, to systematize an appropriate methodology; and concerning to MATLAB, to develop the app on that platform. once the app was realized, it was proceeded to validate through experimental and manual methods (analytically), in addition, for the application user it was elaborated an "User's manual", that will allow to guide the access and correct use of the application.